Widespread occurrence of retinoids in water bodies associated with cyanobacterial blooms dominated by diverse species - Sehnal, Luděk; Procházková, Tereza; Smutná, Marie; Kohoutek, Jiří; Lepšová-Skácelová, Olga; Hilscherová, Klára (Water research, 2019)
Cyanobacterial blooms represent a worldwide problem in freshwater as well as marine ecosystems as producers of various toxic compounds. This study provides environmentally important information about the common presence of mixtures of retinoids in various water bodies associated with the occurrence of cyanobacterial blooms dominated by many different species. The study documents, for the first time, that retinoids are produced by environmental cyanobacterial blooms dominated by species belonging to different genera such as Microcystis, Dolichospermum, Planktothrix, Woronichinia, Pseudanabaena and others. Samples of biomass of cyanobacterial blooms and their surrounding water were collected from seventeen independent freshwater bodies across the Czech Republic during summer 2015. Retinoid-like activity was detected by an in vitro reporter gene bioassay in water samples from 8 out of 17 localities with a maximal activity of 263 ng all-trans retinoic acid equivalent (REQ)/L. In comparison, in vitro assessment of biomass extracts documented retinoid-like activity at 11 out of 17 localities with a maximal retinoid-like activity of 867 ng REQ/g dry mass (dm). Individual retinoids were detected by chemical analyses in all water samples and in 16 out of 17 biomass samples with 4keto-retinal and all-trans 5,6epoxy retinoic acid being detected in aquatic ecosystems for the first time. Further, all-trans 4keto retinoic acid and retinal were the most commonly detected compounds in both types of samples. With respect to retinoid-like activity, a large proportion was explained in some samples by contributions of individual detected retinoids calculated from their concentrations and relative potencies. However, results also indicate that other unknown compounds with a retinoic acid receptor-mediated mode of action were present. The revealed widespread production of retinoids by cyanobacterial blooms dominated by diverse species across various aquatic ecosystems and their common presence in both biomass and surrounding water raises concern namely because some retinoids belong to the most potent teratogens. These compounds need to be taken into consideration in the assessment of risks associated with massive cyanobacterial blooms.
Keywords: Microcystis; Cyanobacteria; Česká republika; retinoidy; Ecosystem; ekosystém; Retinoids; sinice; Czech Republic